(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
In this paper the perspectives of structural colored fibers based on photonic crystal structures are discussed. These fibers display the distinctive colors, which are determined by the lattice constants of the photonic crystals. The color-changing capability of photonic fibers with potential applications in dynamic signage and environmentally adaptive coloration is demonstrated. The fibers are fabricated by the silica or polystyrene colloidal particles to the periodically ordered interconnecting structure in a cylindrical shape. The visible light is coherently diffracted on the surface of the fibers, which produces a shinning color in a narrow range of wavelength. Importantly, no dyes or colorants are used in fabrication of such fibers, thus making the fibers resistant to color fading. This method of making colorful fibers could be a promising way to reduce environmental pollution in the dying industry. Additionally, by changing the reflective index or lattice constant of a photonic fiber, its reflected colors change proportionally to the shift of reflective index or lattice constant, thus enabling visually interactive and sensing textiles responsive to the external stimuli.